Rational Design of Efficient Heavy-Atom-Free Boron-Dipyrromethene Nanophotosensitizers for Two-Photon Excited Photodynamic Therapy of Cancer - Nguyen, Van Nghia; Lee, Dong Joon; Zhang, Dianqi; Ha, Jeongsun; Swamy, Kunemadihalli Mathada Kotraiah; Wang, Rui; Kim, Hwan Myung; Yu, Fabiao; Yoon, Juyoung (Chemistry of Materials, 2024)
Although boron-dipyrromethene (BODIPY) dyes have been widely recognized for their potential use as photosensitizers (PSs) in cancer treatment, the development of heavy-atom-free BODIPY PSs for photodynamic therapy (PDT), particularly in two-photon excited photodynamic therapy (2PE-PDT), remains challenging. Herein, a novel heavy-atom-free photosensitizer (BDP-6) with optimized singlet-triplet energy gap and steric hindrance was designed and synthesized to facilitate intersystem crossing and improve fluorescence intensity. To enhance the biocompatibility and tumor-targeting ability of BDP-6, corresponding nanophotosensitizers (BDP-6 NPs) were prepared by encapsulating BDP-6 within DSPE-PEG(2000) biotin. Compared to control BDP-5 NPs without dimethyl groups, BDP-6 NPs exhibited brighter deep red fluorescence and higher efficiency in generating reactive oxygen species (ROS) under one-photon excitation in aqueous solutions. Moreover, BDP-6 NPs displayed excellent tumor-targeting ability, bright red emission, and considerable phototoxicity with low dark toxicity toward cancer cells. Notably, under two-photon excitation, the BDP-6 NPs efficiently generated ROS both in aqueous solutions and living cells, thereby demonstrating exceptional performance in 2PE-PDT for cancer cell ablation. Furthermore, in vivo experiments revealed that BDP-6 NPs hold great promise for cancer PDT. Our work presents practical strategies for developing tumor-targeting heavy-atom-free nanophotosensitizers based on BODIPY dye for 2PE-PDT of cancer.
Keywords: Boron dipyrromethene; Cancer cells; Heavy atoms; Photosensitiser; Rational design; Reactive oxygen species; Singlet-triplet energy gap; Steric hindrances; Tumor-targeting; Two-photon excited